2009
DOI: 10.1128/iai.00566-08
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Cytokines Induced by Chlamydia pneumoniae Decrease the Expression of Interstitial Collagens and Fibronectin in Fibroblasts

Abstract: Chlamydia pneumoniae infection has been associated with chronic obstructive airway disease (COPD), asthma, and atherosclerosis. Inflammation and airway remodeling in asthma and COPD result in subepithelial fibrosis that is characterized by the deposition of interstitial collagens and fibronectin. The progression of atherosclerosis is also accompanied by an increased production of interstitial collagens in the intima. As shown by reverse transcription-PCR and immunoblotting, infection of human fibroblasts and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…While respiratory infection is often subclinical or mildly symptomatic, chronic infection with C. pneumoniae has been suggested as a trigger or promoter of a number of inflammatory conditions, including asthma (reviewed in [12], [13]), chronic obstructive pulmonary disease (COPD) [14], and atherosclerosis (reviewed in [15]). The mechanism by which C. pneumoniae can disseminate from the lung remains unproven, but one leading model suggests that replication within lung macrophages provides a unique niche for transport to distant sites, such as chronic vascular lesions (reviewed in [15]), and case reports have identified C. pneumoniae within atherosclerotic lesions [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…While respiratory infection is often subclinical or mildly symptomatic, chronic infection with C. pneumoniae has been suggested as a trigger or promoter of a number of inflammatory conditions, including asthma (reviewed in [12], [13]), chronic obstructive pulmonary disease (COPD) [14], and atherosclerosis (reviewed in [15]). The mechanism by which C. pneumoniae can disseminate from the lung remains unproven, but one leading model suggests that replication within lung macrophages provides a unique niche for transport to distant sites, such as chronic vascular lesions (reviewed in [15]), and case reports have identified C. pneumoniae within atherosclerotic lesions [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that C/EBPβ and C/EBPγ participated in skin fibrosis through different mechanisms [249,250] (Figure 8). In dermal fibroblasts, Col1α1 and Col1α2 are target genes of C/EBPβ and increased C/EBPβ expression induced by inflammatory factors, such as interferon beta (IFN-β) and IFN-γ, inhibits not only Col1α1 and Col1α2 expression but also the levels of Col3α1 and fibronectin, which suppresses ECM deposition [210,211,361]. In addition, a recent report showed that C/EBPγ can promote skin wound healing, indicating that C/EBPγ may play an important role in fibroblast activation.…”
Section: C/ebps In Neuralmentioning
confidence: 99%
“…However, C/EBP β protein level is also induced by IL-1 β in lung fibroblasts, with a greater increase in C/EBP β -LIP isoform expression leading to a reduced LAP/LIP ratio and reduced α -SMA promoter activity and expression [ 209 ]. This may explain why treatment with inflammatory factors increases C/EBP β expression and decreases fibroblast activation [ 210 , 211 ].…”
Section: Roles Of C/ebps In the Fibrotic Processmentioning
confidence: 99%
“…While most respiratory-acquired infections are asymptomatic or mild, it can result in pneumonia, usually involving a single lobe, and complications including life-threatening pneumonia and acute respiratory distress syndrome have been reported [ 4 6 ]. In addition, a number of human and animal studies suggest that C. pneumoniae infection can trigger or promote chronic inflammatory conditions, including reactive airway disease and adult-onset asthma (reviewed in [ 7 , 8 ]), chronic obstructive pulmonary disease [ 9 ], and atherosclerosis (reviewed in [ 10 12 ]).…”
Section: Introductionmentioning
confidence: 99%